The heterocyst differentiation transcriptional regulator HetR of the filamentous cyanobacterium Anabaena forms tetramers and can be regulated by phosphorylation. Issue 4 (9th December 2015) - Valladares, Ana; Flores, Enrique; Herrero, Antonia
Summary: Many filamentous cyanobacteria respond to the external cue of nitrogen scarcity by the differentiation of heterocysts, cells specialized in the fixation of atmospheric nitrogen in oxic environments. Heterocysts follow a spatial pattern along the filament of two heterocysts separated by ca. 10–15 vegetative cells performing oxygenic photosynthesis. HetR is a transcriptional regulator that directs heterocyst differentiation. In the model strain A nabaena sp. PCC 7120, the HetR protein was observed in various oligomeric forms in vivo, including a tetramer that peaked with maximal hetR expression during differentiation. Tetramers were not detected in a hetR point mutant incapable of differentiation, but were conspicuous in an over‐differentiating strain lacking the PatS inhibitor. In differentiated filaments the HetR tetramer was restricted to heterocysts, being undetectable in vegetative cells. HetR co‐purified with RNA polymerase from A nabaena mainly as a tetramer. In vitro, purified recombinant HetR was distributed between monomers, dimers, trimers and tetramers, and it was phosphorylated when incubated with (γ‐ 32 P)ATP. Phosphorylation and PatS hampered the accumulation of HetR tetramers and impaired HetR binding to DNA. In summary, tetrameric HetR appears to represent a functionally relevant form of HetR, whose abundance in the A nabaena filament could be negatively regulated by phosphorylation and by PatS. Abstract : Under nitrogen deficiency, certain cells in the filament of the cyanobacterium Anabaena differentiate into heterocysts specialized in nitrogen fixation. Differentiation requires the transcription factor HetR and is inhibited by a PatS peptide, which is synthesized in the differentiating cells and transferred to their neighbors. We show that HetR forms tetramers, which increase in abundance during heterocyst differentiation and are relevant for transcriptional regulation, and that tetramer formation is hampered by HetR phosphorylation and PatS binding.